Modulation of the interfacial electrochemistry of surfactant-functionalised polypyrrole chemical sensor systems - Iftikhar, Faiza J.; Baker, Priscilla G. L.; Baleg, Abdul M.; Ndangili, Peter M.; Mailu, Stephen N.; Iwuoha, Emmanuel I (Pergamon, 2011)
The redox properties of electro-polymerized polypyrrole (Ppy) doped with different surfactants were studied in acid medium. It was found out that the addition of different surfactants affect the redox properties as evidenced by diffusion coefficients and rate constants calculated from experimental data obtained from cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Three different surfactants were incorporated into polypyrrole matrix to form homogeneous composites i.e. anionic surfactant polyvinylsulphonic acid (PVSA) as well as non-ionic surfactants (polyethylene glycol p-(1,1,3,3-tetramethylbutyl)-phenyl ether (Triton-X 100) and polyoxyethylene (20) sorbitan monolaurate (Tween 20). CV and EIS experiments were carried in the presence of the redox probe K3[Fe(CN)6]. Diffusion coefficient was interpreted as a measure of electron movement within the composite polymer structure and rate constant was interpreted as a measure of the rate of oxidation and reduction of the redox probe. The highest value for diffusion coefficient and rate constant was obtained for Ppy/PVSA as 8.16 × 10−12 cm2 s−1 and 1.05 × 10−5 cm s−1 respectively. The values obtained by CV and EIS were in good agreement.
Keywords: Polypyrrole; Surfactants; Diffusion coefficients; Electrochemical impedance spectroscopy; Cyclic voltammetry